Dengan Filsafat Islam Sebagai Alat Menganalisa Secara Kritis Paradigma - Sriyono Fauzi; Warih Nurul Hidayati; Solekhah Nur Afifah; Nur Ali Rahmatullah (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
The position of philosophy in Islam throughout history has experienced ups and downs of glorification and criticism. It is inevitable that when we discuss the position and even function of philosophy in the Islamic Studies approach, issues surrounding the harmonization of philosophy and religion will become the center of attention. Thus, Islamic education is a paradigm or educational model that is based on the values ​​of Islamic teachings. This education model has integrated its education system with an ideology that is based on the Koran and Sunnah as the main source of Islamic teaching principles.